Molecularly imprinted solid-phase extraction for the determination of ten macrolide drugs residues in animal muscles by liquid chromatography–tandem mass spectrometry. (1st October 2016) - Song, Xuqin; Zhou, Tong; Liu, Qingying; Zhang, Meiyu; Meng, Chenying; Li, Jiufeng; He, Limin
Highlights: The MIP was synthesized and used as a packing of solid-phase extraction. LC–MS/MS was used for the determination of macrolide drugs residues in muscles. Mean recoveries for ten macrolides were from 60.7% to 100.3% with RSD <14%. The limits of detection for ten macrolides were between 0.1 and 0.4 μg kg −1 . Abstract: A simple and sensitive method based on molecularly imprinted solid-phase extraction coupled with liquid chromatography–tandem mass spectrometry was developed for the determination of the residues of ten macrolide drugs in swine, cattle and chicken muscles samples. The molecularly imprinted polymers (MIPs) were synthesized using tylosin as a template and methacrylic acid as a functional monomer. Samples were extracted with sodium borate buffer solution and ethyl acetate, and purified by the MIP cartridge. The results showed that the cartridge exhibited good recognition performance for macrolides, and better purification effect than the traditional solid-phase extraction cartridges. Recoveries of analytes at three spiking levels 1, 5 and 20 μg kg −1 ranged from 60.7% to 100.3% with the relative standard deviations less than 14%. The limits of detection of the method were between 0.1 and 0.4 μg kg −1 . The method is useful for the routine monitoring of the residues of macrolide drugs in animal muscles.